Enhancement of structural, functional and antioxidant properties of fish gelatin films using Maillard reactions. (October 2018) - Kchaou, Hela; Benbettaïeb, Nasreddine; Jridi, Mourad; Abdelhedi, Ola; Karbowiak, Thomas; Brachais, Claire-Hélène; Léonard, Marie-Laure; Debeaufort, Frédéric; Nasri, Moncef
Abstract: This study investigates the effect of Maillard reactions (MR) on the physico-chemical and biological properties of fish gelatin based edible films. Glucose was incorporated in gelatin film forming solutions at different glucose/lysine molar ratios: 0.5/1.0, 1.0/1.0 and 5.0/1.0. The MR was then induced by heating films at 90 °C for 24 h in dry conditions. Color changes and browning index measurements were used to pursue the MR kinetic. Results showed that the development of MR products was dependent on the glucose content and on the reaction time. Mechanical and thermal properties of treated films displayed an increase in tensile strength, elongation at break and glass transition temperature with the glucose addition and heating time. In addition, barrier properties against UV light and water resistance (water solubility and water contact angle measurements) increased due to the gelatin-glucose interactions generated at high temperature. The in vitro antioxidant activity of fish gelatin films modified by MR was studied by using DPPH free radical scavenging, total antioxidant activity and the reducing power. The antioxidant activity was significantly enhanced with mainly the glucose content and, in a less extent, with the reaction time. Consequently, fish-gelatin based films cross-linked through the Maillard reactions pathway are promising for food edible packaging materials to protect products toward oxidation. Graphical abstract: Image 1 Highlights: Generation of bioactive compounds by Maillard reaction in Fish gelatin edible films. Glucose/lysine ratio influenced significantly the film properties. Physical-chemical properties enhanced by Maillard reaction due to favored crosslinking. Fish gelatin films exhibit significant antioxidant properties (up to x5) after Maillard reaction treatment.